2012
DOI: 10.1186/1746-6148-8-202
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of congenital hereditary sensorineural deafness in Australian Cattle Dogs and associations with coat characteristics and sex

Abstract: BackgroundCongenital hereditary sensorineural deafness (CHSD) occurs in many dog breeds, including Australian Cattle Dogs. In some breeds, CHSD is associated with a lack of cochlear melanocytes in the stria vascularis, certain coat characteristics, and potentially, abnormalities in neuroepithelial pigment production. This study investigates phenotypic markers for CHSD in 899 Australian Cattle Dogs.ResultsAuditory function was tested in 899 Australian Cattle Dogs in family groups using brainstem auditory evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Brain stem auditory evoked response (BAER) testing distinguishes bilaterally and unilaterally hearing-impaired dogs from non-affected animals [ 161 ]. BAER data have been used to report prevalence estimates for deafness in Dalmatians [ 162 ], Border Collies [ 163 ] and Australian Cattle Dogs [ 164 ] as well as across multiple breeds [ 165 ]. These studies benefitted from well-defined case inclusion criteria and large study sizes but the voluntary submission process may have affected the presentation probabilities for known deaf individuals.…”
Section: Reviewmentioning
confidence: 99%
“…Brain stem auditory evoked response (BAER) testing distinguishes bilaterally and unilaterally hearing-impaired dogs from non-affected animals [ 161 ]. BAER data have been used to report prevalence estimates for deafness in Dalmatians [ 162 ], Border Collies [ 163 ] and Australian Cattle Dogs [ 164 ] as well as across multiple breeds [ 165 ]. These studies benefitted from well-defined case inclusion criteria and large study sizes but the voluntary submission process may have affected the presentation probabilities for known deaf individuals.…”
Section: Reviewmentioning
confidence: 99%
“…The boxer Tasha that was used to sequence the canine genome had a phenotype designated as flash ( Ss w ), which enabled construction of BACs (bacterial artificial chromosomes) for each allele from her DNA ( 74 ). Significant associations between deafness and the recessive piebald alleles have been demonstrated for Dalmatian, English setter, and English cocker spaniel ( 75 ), border collie ( 76 , 77 ), Australian cattle dog ( 78 ), and Jack Russell terrier ( 79 ). It has also been shown that a strong relationship exists between deafness and the absence of pigment in the iris and tapetum lucidum, interpreted to be evidence of strong expression of the piebald locus ( 75 ).…”
Section: Deafness In Domestic Animal Speciesmentioning
confidence: 99%
“…Several studies have evaluated the prevalence of CSD in predisposed breeds in particular geographical areas 9 14–20. Prevalence ranges widely from 1.3 per cent in whippets9 to 30 per cent in dalmatians 9.…”
Section: Introductionmentioning
confidence: 99%
“…Some phenotypic characteristics have been found to be significantly associated with CSD in particular breeds of dog. These are generally traits associated with lack of pigmentation such as blue eyes or white coat 9 14 16 17 19. Some studies in dalmatians have reported a higher prevalence of CSD in females,21–24 but others25 26 have found no difference.…”
Section: Introductionmentioning
confidence: 99%